Evaluating barriers to digital libraries development: Insights from Interpretive Structural Modeling (ISM) and Cross-Impact Matrix Multiplication (MICMAC) - Raju, Roshan; R.K. Kishore Patnala (Malaysian Journal of Library and Information Science, 2024)
Digital libraries are pivotal in advancing knowledge accessibility, yet their development faces significant obstacles, particularly in developing regions like India. This study evaluates the barriers to digital library development using Interpretive Structural Modeling (ISM) and Cross-Impact Matrix Multiplication (MICMAC) analysis. Data were gathered from eight domain experts in India, who identified 10 critical barriers, including the lack of institutional policy, which emerged as the most critical barrier to adopting digital libraries. As an independent factor, it sits at the bottom of the digraph model created by ISM, serving as the foundational barrier. Another major barrier is the lack of financial resources, which significantly hinders development due to the substantial costs involved in digital library initiatives for academic institutions. Additionally, barriers such as lack of management support, physical infrastructure, and technological infrastructure further exacerbate the challenges. ISM was employed to construct a hierarchical model revealing the interrelationships and driving power of these barriers, while MICMAC analysis categorised them based on their influence and dependencies. The findings emphasise the importance of addressing foundational barriers to ensure resilient and effective digital library systems in India.